Staffs perceptions of important indicators and self-assessment of hospital food service operations performance - Osman, Noor Suzana; Md Nor, Norazmir; Ishak, Ruzaina (International Islamic University Malaysia, 2025)
Background: Enhancing hospital food services performance can be challenging as identifying components that influence accurate evaluation is a critical element of organisational success.Thus, this study was conducted to assess staff perceptions of key performance indicators and their selfevaluation on the performance of hospital food service operations. Methods: This cross-sectional survey was conducted using a validated and reliable self-administered questionnaire. Respondents were selected from the food service staffs at Malaysian hospitals based on specific inclusion and exclusion criteria. The data analysis was performed using IBM SPSS version 26.0 software. The sociodemographic data was examined, and the means of importance and performance indicators were compared using a paired-sample t-test. The IPA grid was generated by integrating the means scores of importance and performance. Results: A total of 160 respondents comprising 35 males (21.9%) and 125 females (78.1%) completed this survey. The gap analysis reveals that eleven indicators demonstrate a significant difference between staff evaluation of hospital food service performance and their perceptions of the importance of food service attributes (p<0.01). Five indicators have been identified by the IPA grid that require improvement in the areas of food production and distribution management, as well as patient and customer service management. Conclusions: The findings suggest that hospital food service providers should focus on using a variety of food ingredients, evaluating their menus, and monitoring the health and cleanliness of their staff in order to improve their service quality.